Sistem Informasi Data Pemantauan Wilayah Setempat Kesehatan Ibu Dan Anak ( KIA) : (Studi Pada Puskesmas Kecamatan Rambang Kabupaten Muara Enim) - hermizahadiwidastra, hermizahadiwidastra (Jurnal Nasional Ilmu Komputer, 2024)
Computer-based data processing has developed greatly. In health institutions such as community health centers, the role of information technology can no longer be separated. Almost all community health centers currently implement computer-based systems to manage health-related data, such as maternal and child health (KIA). With a computerized system, we can provide good and fast service and present information effectively and efficiently. This requires the ability of human resources to master and follow developments in science and technology; the development of science is always followed by technological advances which are needed in data processing, namely by using computer tools and programs, data processing will be carried out well and the results Perfect.